The state of lipid exchange and thrombotic link of hemostasis in patients with chronic non-specific inflammatory diseases of genitals - Sokolovskaya, I. A.; Maryukhnich, N.; Zarytska, V.; Kyrpychenko, O.; Nechiporenko, V.; Pozdnyakova, O.; Gordiyenko, N.; Tsymbal, V.; Соколовська, Ірина Анатоліївна (My University, 2019)
It has been stated that changes of lipid exchange and increasing of lipid peroxidation are accompanied by the inflammatory process, which show the increase of proatherogenic blood characteristics. In patients with chronic non-specific inflammatory diseases of genitals disorders of phagocytosis mechanisms, increasing of autointoxication and reaction of hypersensitivity of immediate type are revealed after full blood count index. On the basis of analyses results one can conclude that the increase of atherogenic properties of blood plasma in patients with chronic non-specific inflammatory diseases of genitals took place in accordance with vascular endothelium damage. The article is the first to show the effectiveness of complex treatment of different atherosclerotic pathogenesis links by means of correction of proatherogenic lipid fractions and antioxidative complexes.
Keywords: lipids; hemostasis; reactivity; chronic non-specific inflammatory diseases of genitals